PENEGAKAN HUKUM TERHADAP PELANGGARAN MENGGUNAKAN KENDARAAN BERMOTOR TIDAK LAIK JALAN YANG MENYEBABKAN KECELAKAAN LALU LINTAS (Studi Kasus pada Satlantas Polres Muna) - Setiawan, Endi; Kamaruddin, Kamaruddin; Samandi, Hariman Satria (Fakultas Syariah INSURI Ponorogo, 2023)
This research investigates the law enforcement concerning traffic accidents caused by unfit motor vehicles in Muna Regency. Employing a normative juridical approach, the study analyzes laws and their connection to real events, focusing on the legal resolution of such accidents. The role of legal culture, encompassing societal behaviors, values, and beliefs, is emphasized, as effective enforcement relies on widespread legal awareness. Specifically, the study examines Article 273 of Law No. 22 of 2009 concerning Traffic and Road Transportation, which addresses criminal sanctions for road administrators. Preliminary analysis suggests potential gaps in its implementation. The research aims to identify the reasons for insufficient enforcement and proposes measures to strengthen law enforcement in Muna Regency. Recommendations may encompass increasing legal awareness, enhancing collaboration among law enforcement agencies, imposing stricter penalties for violations, and implementing more efficient monitoring systems. Ultimately, this study seeks to enhance legal enforcement strategies and promote road safety in Muna Regency by addressing challenges associated with unfit motor vehicle-related accidents. Understanding and tackling the root causes of ineffective enforcement will enable policymakers and stakeholders to develop targeted interventions, reduce accidents, and ensure proper application of the law.